2019
DOI: 10.1242/jcs.224212
|View full text |Cite
|
Sign up to set email alerts
|

Message in a vesicle – trans-kingdom intercommunication at the vector–host interface

Abstract: Vector-borne diseases cause over 700,000 deaths annually and represent 17% of all infectious illnesses worldwide. This public health menace highlights the importance of understanding how arthropod vectors, microbes and their mammalian hosts interact. Currently, an emphasis of the scientific enterprise is at the vector-host interface where human pathogens are acquired and transmitted. At this spatial junction, arthropod effector molecules are secreted, enabling microbial pathogenesis and disease. Extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 93 publications
(137 reference statements)
0
24
0
Order By: Relevance
“…The molecular and cellular events occurring in vector-pathogen-host interactions are critical in determining the outcome of the vector-borne diseases. Recently, it was proposed that one strategy used by vectors, to promote a successful host infection, is the manipulation of EVs [41,57]. Infected vector cells secrete vesicles that may contain antigens, nucleic acids, and microbial cargos (or the whole pathogen), which exacerbate the pathogenesis and modulate the host responses [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular and cellular events occurring in vector-pathogen-host interactions are critical in determining the outcome of the vector-borne diseases. Recently, it was proposed that one strategy used by vectors, to promote a successful host infection, is the manipulation of EVs [41,57]. Infected vector cells secrete vesicles that may contain antigens, nucleic acids, and microbial cargos (or the whole pathogen), which exacerbate the pathogenesis and modulate the host responses [36].…”
Section: Discussionmentioning
confidence: 99%
“…Since the optimal cell infections (activation) were obtained in these conditions (MOI 1, 48 h PI), they were used for all subsequent infection experiments. Recently, it was shown that, during the virus infection process, infected cells are activated and produce different subtypes of EVs, which may have different functions when interacting with other cells, modifying naïve cellular behavior [41]. Therefore, we evaluated whether ZIKV-infected C6/36 mosquito cells could release large and/or small EVs.…”
Section: Zikv Infects C6/36 Mosquito Cellsmentioning
confidence: 99%
“…As such, exosomes that carry microRNAs has been described in the saliva of ticks (Hackenberg et al, 2017 ). It has been proposed that these exomes may deliver microRNAs to immune cells to down-regulate immune modulatory pathways (Hackenberg and Kotsyfakis, 2018 ; Bensaoud et al, 2019b ; Chávez et al, 2019 ). This will add another layer of complexity to salivary glands of which the magnitude is difficult to estimate.…”
Section: Other Measures Of Complexity: Alternative Splicing Recombinmentioning
confidence: 99%
“…Hard tick salivary glands suffer a degeneration process after a blood meal (Harris and Kaufman, 1981 ; Friesen and Kaufman, 2009 ), and it is possible that this process starts while the tick is still feeding and thus generating a holocrine salivary secretion. Additionally, there is recent evidence that exosomes may be secreted in tick saliva (Hackenberg and Kotsyfakis, 2018 ; Zhou et al, 2018 ; Chavez et al, 2019 ). Exosomes can fuse with host cells and deliver their products intracellularly, including microRNAs that may inhibit translation of some protein types (Keller et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%